Contextual Teaching and Learning to Improve Mathematics Interest and Achievement: A Study in Indonesian Elementary Schools - Sri Yusriani; Shine Pintor Siolemba Patiro (Universitas Muhammadiyah Purwokerto, 2026)
In today’s digital era, many students exhibit low interest in mathematics, which often hampers their overall academic performance. This study investigates the effectiveness of a Contextual Teaching and Learning (CTL) approach in enhancing students’ engagement and enthusiasm for mathematics. The research involved 58 sixth-grade students from two elementary schools in Palembang and Tangerang, Indonesia. A quantitative design was employed, utilizing pre-tests, post-tests, feedback sheets, and structured questionnaires to assess changes in student participation and understanding. The findings revealed a substantial improvement in students’ comprehension and motivation, with average scores increasing from 58.21 (pre-test) to 89.29 (post-test). Feedback and questionnaire analyses further demonstrated positive responses, with success rates exceeding 78% and 82%, respectively. These results suggest that integrating CTL strategies into mathematics instruction can effectively promote active participation and deepen conceptual understanding. The study recommends that educators adopt interactive learning models to foster stronger engagement in mathematics.